The Impact of the Use of Technology in International Rail Freight Transport on Transport Processes - Židová, Zuzana; Vladislav Zitrický (Promet, 2023)
Transport is an integral part of any company. Nowadays, there is a great emphasis on the use of environmentally friendly modes of transport. In addition to being one of the environmentally friendly modes of transport, rail transport can carry large quantities of various goods over long distances. In order for rail transport in Slovakia to be able to compete with other modes of transport, it is important that Industry 4.0 elements are applied in the technological processes at railway stations. The aim of this article is to draw attention to the impact of the introduction of Industry 4.0 elements into the transport process in rail transport. The premise of the research task is based on the experience with the introduction of intelligent sensors in rail transport in some European Union countries. On the basis of the analysis of the use of information and communication technologies in railway transport, the article carries out a technological evaluation of the design of the wagon control unit in the transport process with regard to the speed of processing a shipment in a border-crossing station.